Somatic embryogenesis and triterpenoid saponin production in Aralia elata (Miq.)Seem. - Cheng, Y.; Liu, H.; Tong, X.; Liu, Z.; Zhang, X.; Jiang, X.; Yu, X.
To establish an efficient regeneration system through somatic embryogenesis of Aralia elata (Miq.)Seem, the effects of explant type and growth regulators on callus induction in A. elata were evaluated. Stems apices were the best explant type for callus induction when cultured on MS medium supplemented with 1.0 mgoL?1 2,4-D, and the highest induction rate (97.78 percent)and callus yield (1.72 g of FWoexplant?1)were achieved with this medium. Indirect somatic embryogenesis was achieved from calli of the A. elata clone "CH02-1-03", and the greatest number of somatic embryos (SEs)per callus percent (166.51 SEog?1 callus)was achieved on MS medium supplemented with 3.0 mgoL?1 IBA in combination with 0.5 mgoL?1 BAP. Somatic embryogenesis and triterpenoid saponins content were significantly influenced by light intensity and the highest of somatic embryogenesis (88.89 percent)and number of SEs per callus (169.17)were achieved under medium light intensity of 2000 lx. While, total saponins and three saponin monomers content were increased with light intensity. To conveniently isolate SEs and prevent secondary SE regeneration, shoots were cut off and transferred to root regeneration medium; shoots rooted best in MS medium with 4.0 mgoL?1 IBA, with 22.67 average roots number and 9.52 root length higher than other groups. Approximately 81.54 percent of the cultured plantlets produced roots, and the plantlets exhibited a 81.11 percent survival rate.